History of Irrigation Sciences in Uzbekistan - Alisher Saydullaevich, Ravshanov; Husniddin Alikulovich, Akhmedov (International Journal of Psychosocial Rehabilitation, 2020)
This article provides information on the scientific achievements, historical experience, and development of theories in the field of irrigation in the territory of Uzbekistan. In order to understand the concepts of sciences that are important in the construction of ancient hydraulic structures, they were analyzed and covered in comparison with the classification of sciences by Ahmad Tashkprizade. The article also provides information on some of the most advanced achievements in the field of irrigated agriculture and construction of hydraulic structures, which are unique to Uzbekistan. Reading this article gives a clear idea of the main features of the development of science in the history of irrigation in Uzbekistan.